KUALITAS PELAYANAN PUBLIK BIDANG PENANAMAN MODAL (STUDI DI KANTOR PELAYANAN TERPADU SATU PINTU) - Angki Sesarrita; Agus Suryono; Sarwono . (Universitas Tribhuwana Tunggadewi, 2015)
Investment is one of main factor on the economic growth increasing at the region. Investor will help government and society make the potential of that region be more function than before. But, the problem is investor always get obstacle like the permit or allowance at that field. It makes investor has uncertaint feeling for processing its investment.Now, government have awareness the significant of public service at investment sector. Then create a concept of one stop service which give the whole of processing at permit and non permit, begin from collecting documents until the publishing of allowance letter worked at one office. So that Government of Blitar Region does the same thing for easiness and simplicitiness at permit and non permit for society and investor.